Ultrasonographic detection of apex nodules in the urinary bladder of Scottish Terriers. Issue 2 (5th January 2022) - Heng, Hock Gan; Ramos‐Vara, José A.; Fulkerson, Christopher M.; Fourez, Lindsey M.; Knapp, Deborah W.
Abstract: An apex nodule was recently identified in the urinary bladder of Scottish Terriers being screened for bladder cancer at our institution. This prospective, single‐center, case series study was performed to better characterize the apex nodule and assess the clinical importance of the nodule. Scottish Terriers ≥6 years of age with no evidence of urinary tract disease underwent urinary tract ultrasonography and urinalysis at 6‐month intervals. In dogs with evidence of the apex nodule, ultrasound features such as location, margins, number, echogenicity, size, and shape of the lesion were recorded by a veterinary oncologist and veterinary radiologist. The apex nodule was identified in eight (6%) of 134 dogs in the absence of other detectable bladder disease. Features of the nodules included the following: one nodule per dog, triangular to an oval shape, smooth mucosal covering, well‐defined margins, isoechoic to the bladder wall, 2–4 mm at the base, and 4–6 mm protruding into the bladder lumen. In five dogs undergoing multiple ultrasonographic examinations, the nodule did not appear to change over time (up to 3.5 years). Cystoscopy performed in three dogs revealed a column of tissue covered by normal mucosa protruding into the bladder lumen. Histological features consistent with a neoplastic growth were absent. Five dogs remained free of any bladder disease. Three dogs developed urothelial carcinoma at sites distant to the nodule at 8–53 months after the nodule was first observed. Findings indicated that incidental apex nodules could mimic neoplasia and other bladder diseases in Scottish Terriers.